Thermally Dependent Dynamic Meta‐Holography Using a Vanadium Dioxide Integrated Metasurface. Issue 12 (14th April 2019) - Liu, Xingbo; Wang, Qiu; Zhang, Xueqian; Li, Hua; Xu, Quan; Xu, Yuehong; Chen, Xieyu; Li, Shaoxian; Liu, Meng; Tian, Zhen; Zhang, Caihong; Zou, Chongwen; et al.
Abstract: Metasurfaces have drawn enormous attention in both the physics and engineering communities owing to their capabilities of arbitrarily manipulating the electromagnetic waves at subwavelength scale. One of the promising applications of metasurfaces is the realization of high‐quality holograms. However, due to the passive response of metasurface resonators, previous demonstrations on meta‐holography were mainly limited to generating static images. Seeking new approaches to realize active control over meta‐holograms is highly demanded for display applications, such as holographic movies. Here, a broadband active meta‐holography which enables temperature‐dependent dynamic holographic imaging is experimentally demonstrated. The meta‐hologram consists of two sets of resonators: set 1 is passive, being composed of simple metallic C‐shape split‐ring resonators (CSRRs) and set 2 is active, being composed of vanadium dioxide (VO2 ) integrated CSRRs (V‐CSRRs). Each set generates certain holographic images with predesigned amplitude and phase distributions. Under external heating, the insulator‐to‐metal transition property of VO2 will gradually short out the V‐CSRRs and their responses, thus dynamically changing the overall generated holographic image. The proposed approach presents a new way of tunable metasurface design and holds promise for active meta‐devices with versatile functionalities. Abstract : Thermally dependent dynamic meta‐holography is experimentally demonstrated by designing the interference between the generated images from the designed C‐shape split‐ring resonators and vanadium dioxide integrated C‐shape split‐ring resonators in the terahertz regime. The proposed method provides a novel way to design active meta‐devices with various functionalities at both terahertz and optical frequencies.